The Effects of Superimposed Whole-Body Electromyostimulation During Short-Term Strength Training on Physical Fitness in Physically Active Females: A Randomized Controlled Trial - Dörmann, Ulrike; Wirtz, Nicolas; Micke, Florian; Morat, Mareike; Kleinöder, Heinz; Donath, Lars (Frontiers in Physiology, 2019)
The aim of this study was to compare the effects of short-term strength training with and without superimposed whole-body electromyostimulation (WB-EMS) on straight sprinting speed (SSS), change of direction speed (CODS), vertical and horizontal jumping, as well as on strength and power in physically active females. Twenty-two active female participants (n = 22; mean ± SD: age: 20.5 ± 2.3 years; height: 171.9 ± 5.5 cm; body mass: 64.0 ± 8.2 kg; strength training experience 5.1 ± 3.6 years) were randomly assigned to two groups: strength training (S) or strength training with superimposed WB-EMS (S+E). Both groups trained twice a week over a period of 4 weeks and differed in the application of free weights or WB-EMS during four strength (e.g., split squats, glute-ham raises) and five sprinting and jumping exercises (e.g., side and box jumps, skippings). The WB-EMS impulse intensity was adjusted to 70% of individual maximal sustainable pain. SSS was tested via 30-m sprinting, CODS by a T-run, vertical and horizontal jumping using four different jump tests at pre-, post-, and retests. Maximal strength (Fmax) and power (Pmax) testing procedures were conducted on the Leg Press (LP), Leg Extension (LE), and Leg Curl (LC) machine. Significant time × group interaction effects revealed significant decreases of contact time of the Drop Jump and split time of CODS (p ≤ 0.043; ηp2 = 0.15–0.25) for S (≤ 11.6%) compared to S+E (≤ 5.7%). Significant time effects (p < 0.024; ηp2 = 0.17–0.57) were observed in both groups for SSS (S+E: ≤6.3%; S: ≤8.0%) and CODS (S+E: ≤1.8%; S: ≤2.0%) at retest, for jump test performances (S+E: ≤13.2%; S: ≤9.2%) as well as Fmax and Pmax for LE (S+E: ≤13.5%; S: ≤13.3%) and LC (S+E: ≤18.2%; S: ≤26.7%) at post- and retests. The findings of this study indicate comparable effects of short-term strength training with and without superimposed WB-EMS on physical fitness in physically active females. Therefore, WB-EMS training could serve as a reasonable but not superior alternative to classic training regimes in female exercisers.